Elaborasi Operasional Akad Murabahah Produk KPR (Kredit Pemilikan Rumah) dalam Perbankan Syariah - Massura Putri Syahru; Anfal Bahri (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This study describes how murabahah for sharia banking KPR products operate as well as murabahah for KPR products that have indications of hilah (legal engineering). This study uses a qualitative method of literature (library research) as a research approach. The findings of this study indicate that Islamic banking has modified the original concept of murabahah contracts, namely that the bank does not yet have a house to sell. The murabahah contract is implemented through murabahah li al-amir bi al-shira' (the buyer requests and authorizes another party to buy an item with certain criteria, then he promises to buy the item throughselling murabahah). This shows that the bank is no longer selling goods, but only representing customers through wakalah. The role of the bank is to support funds, not to enter into a sale and purchase contract. So that shows that the murabahah of Sharia KPR is formulated through the hilah based on the indications and parameters of hilah. However, hilah on murabahah are categorized as hilah masyru'ah (hilah are allowed). It can be concluded that the murabahah of Sharia KPR can be used for a limited time, but it is not an ideal contract concept to be used for a long time.